Manajemen Asesmen Nasional Berbasis Komputer (ANBK) Semi Online di SD IT Al Furqan Palangka Raya - Aulia Kiftiah Kencana; Normakiah Ramadan; Khairi Yannur; Yugi Saputra; Sapuadi Sapuadi (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
This study examines the semi-online Computer-Based National Assessment (ANBK) management at SD IT Al Furqon Palangka Raya which is studied from the aspect of planning, organizing, implementing and supervising that contribute to the success of a policy or educational institution in which there are efforts to influence each other, mobilize and supervise each other. The research method used is descriptive qualitative, the research subjects are school principals, vice principals in the field of curriculum and proctors who are involved. The results of the study show that from the planning stage it can be explained that SD IT Al Furqan carried out various stages of preparation by demanding rapid adaptation of all supporting components within the dd.school scope, starting from financing planning, human resources who served as proctor, technicians and supervisors. , and facilities and infrastructure. At the organizing stage (organizing) the school allocates tasks according to their respective duties and functions.implementation (actuating) of semi-online ANBK has been carried out according to guidelines and procedures starting from semi-online preparation, providing all the needs of semi-online ANBK for the successful implementation of activities. At the controlling stage , the school checks in detail, starting from the skills of proctors and technicians to the availability of networks and other installations.